Joint Land Certification, Gendered Preferences, and Land-related Decisions: Are Wives Getting More Involved? - Stein Holden; Sosina Bezu (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
We have investigated whether joint land certification in Southern Ethiopia has contributed to a strengthening of the perceived land rights of women and an increase in their intra-household involvement in land-related decisions. We use gender-disaggregated household panel data and generate indices for wives' and husbands' land rights attitudes and for wives' involvement in land-related decisions. After controlling for endogeneity of land certification, using a Control function approach, we find that receipt of land certificate has strengthened wives' awareness of their land rights. We also find evidence of an intra-household bargaining effect and an intracommunity social process effect that both contribute to stronger involvement of wives in landrelated decisions within households.
Keywords: D03; J16; Q15; 330; joint land certification; gender; empowerment of wives; Ethiopia